2010
DOI: 10.1371/journal.pone.0013824
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss in Stranded Odontocete Dolphins and Whales

Abstract: The causes of dolphin and whale stranding can often be difficult to determine. Because toothed whales rely on echolocation for orientation and feeding, hearing deficits could lead to stranding. We report on the results of auditory evoked potential measurements from eight species of odontocete cetaceans that were found stranded or severely entangled in fishing gear during the period 2004 through 2009. Approximately 57% of the bottlenose dolphins and 36% of the rough-toothed dolphins had significant hearing defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 32 publications
0
39
4
1
Order By: Relevance
“…Alhoewel visserij minder problematisch is binnen de wateren van Caribisch Nederland (maar meer direct daarbuiten, zoals Venezolaanse wateren), neemt menselijke verstoring wel gestaag toe (Debrot et al, 2011b), met aantoonbaar negatieve effecten, zoals aanvaringen en gehoorschade met strandingen tot gevolg (Mann et al, 2010;Luksenburg, 2014). Daarvoor dienen wettelijke richtlijnen te worden opgesteld en dient verder onderzoek te worden gedaan naar de mate van antropogene geluidsbelasting in zee (Risch en de Haan, 2016).…”
Section: Verstoringunclassified
“…Alhoewel visserij minder problematisch is binnen de wateren van Caribisch Nederland (maar meer direct daarbuiten, zoals Venezolaanse wateren), neemt menselijke verstoring wel gestaag toe (Debrot et al, 2011b), met aantoonbaar negatieve effecten, zoals aanvaringen en gehoorschade met strandingen tot gevolg (Mann et al, 2010;Luksenburg, 2014). Daarvoor dienen wettelijke richtlijnen te worden opgesteld en dient verder onderzoek te worden gedaan naar de mate van antropogene geluidsbelasting in zee (Risch en de Haan, 2016).…”
Section: Verstoringunclassified
“…Hearing loss has previously been documented in odontocete species in both captive (Ridgway and Carder, 1997;Brill et al, 2001;Finneran et al, 2005b;Yuen et al, 2005;Houser and Finneran, 2006;Houser et al, 2008) and stranded conditions (Mann et al, 2010). Assuming that the auditory system of odontocetes is similarly subject to impairment/hearing loss as reported in humans and other mammals, hearing loss in odontocetes can be caused by intense chronic noise, transient intense noise exposure, congenital hearing impairment, physical trauma, infections of the inner ear, ototoxic drug treatment and presbycusis (Tarter and Robins, 1990).…”
Section: Discussionmentioning
confidence: 97%
“…It follows that hearing loss in odontocetes is an increasingly important consideration. While there is some information on the fundamental hearing ability of many odontocete species (Au et al, 2000;Mooney et al, 2012), hearing loss has only been investigated and demonstrated in a few species in captivity (Ridgway and Carder, 1997;Brill et al, 2001;Finneran et al, 2005b;Yuen et al, 2005;Houser and Finneran, 2006;Houser et al, 2008) or while stranded (Mann et al, 2010). Little is known about the incidence and cause of the reported hearing loss in odontocetes, and differences across species and habitat conditions.…”
Section: Introductionmentioning
confidence: 99%
“…pulses. Van Bree and Kristensen (1974) were the first to suggest that naval exercise-related marine noise might be a cause of mortality of cetaceans in the Dutch Caribbean while Mann et al (2010) appear to have determined an instance of hearing loss as a potential cause of stranding of a pilot whale in Curaçao.…”
Section: Figure 12mentioning
confidence: 99%